Mindful minds and entrepreneurial spirits in higher education: a scoping review - Karali, Nansy; Mastrokoukou, Sofia; Livas, Christos (Frontiers in Education, 2023)
Introduction: Mindfulness at Higher Education Institutions (HEIs) may enhance personal development, learning, and entrepreneurial thinking. Thus, this scoping review investigates the effects of mindfulness on HEI entrepreneurship education, focusing on teaching, learning, and entrepreneurial intention. Method: To identify relevant articles for inclusion, the study used a predetermined set of keywords and a descriptive search algorithm in six electronic databases. The process of study selection adhered to the principles outlined in the Preferred Reporting of Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, and resulted in the inclusion of eleven (11) studies. Said studies spanned several nations and employed various research methods, with an emphasis on quantitative approaches. Results: Results indicated that mindfulness did not have a direct impact on lecturers’ commitment to teaching entrepreneurship. Nevertheless, mindfulness appeared to indirectly impact teaching outcomes by influencing other variables, such as readiness for change. From an educational processes and outcomes perspective, mindfulness was found to improve the entrepreneurship learning environment and enhance students’ entrepreneurial orientation. The latter included students’ intentions to develop or participate in environmental and socially responsible entrepreneurial ventures. Discussion: The present study advances our understanding of the relationship between mindfulness, entrepreneurship teaching and students’ entrepreneurial orientation in higher education settings. Nevertheless, it also demonstrates a lack of comprehension of the exact mechanisms at play, and therefore highlights the need for further research in this scientific area. By gaining a broader awareness of the impact of mindfulness on entrepreneurship education, education professionals and decision-makers can improve the design of programs to cultivate the entrepreneurial orientation and skills necessary for students’ success in a rapidly changing business environment.